SIMULASI ANTRIAN PINTU TOL DENGAN MENGGUNAKAN PEMROGRAMAN KOMPUTER (Studi Kasus Pintu Tol Cililitan) - ANDRIYANTO, AGUNG ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The problem that occurs in the toll gate is long queues and delays, so that service becomes less effective in the toll gate. The arrival of the vehicle in the toll gate is a random variable value, so need a simulation and modeling to describe the traffic situation in the toll gate services. This study objective is to provide simulation and modeling in the process of servicing the toll gate. This study calculate the value of delays and queues length in a toll gate service. The study was conducted by direct observation of the state of the toll and then built a computer program that can provide ease of simulation and modeling with the condition. Factors that affect the amount of delays and queues in the toll gate is the arrival vehicle, service time, the length of the vehicle, vehicle composition and length of vehicles entering the toll gate. The results showed that the simulation results and the results of the field survey program was not a significant difference, so the simulation results of the program can be used for process simulation in other places. Computer programs can be used to simulate solutions that generate value delay and queue length efficiently and improve the quality of service the toll gate.